Understanding autistic relationships across the lifespan family, friends, lovers and others - Sedgewick, Felicity; Douglas, Sarah (Autism study advisor) (Routledge, 2023)
"Understanding Autistic Relationship across the Lifespan is an accessible overview of autistic relationships from the early years through to old age. This much-needed book combines the latest research findings with first-hand accounts to offer insight into the relationships of autistic people and how they differ to those of non-autistic people in a range of ways. Felicity Sedgewick and Sarah Douglas delve into life's stages and their challenges, revealing how navigating relationships can lead to misunderstandings, rejection, and trauma - but also to genuine connection, support, and joy. Illustrated throughout with extracts from interviews, and with extended narratives from Sarah, it explores key topics including: Relationships in the early years, childhood friendships, teenage friendships and romance, adult romantic and sexual relationships, LGBTQ+ relationships, finding community, family relationships, and issues in the later stages of life. The authors explore a wide range of emotions and life situations, examining the social world of autistic people and the strategies they use to navigate it. Understanding Autistic Relationship across the Lifespan offers practical recommendations for both autistic and non-autistic people on how to have the healthiest and most satisfying relationships possible. It is essential reading for all those working with autistic people and studying autism, as well as autistic individuals and those close to them"--